Behind the scenes of controversial International Commercial Arbitration: Case Study of Heirs to the Sultanate of Sulu v. Malaysia - Ong, Tze Chin; Wen, James Ding Tse (Indonesian Journal of International Law, 2023)
Recently, an ad hoc arbitration final award of US$14.92 billion (approximately RM62.59 billion) in favour of the heirs of the 19th-century sultanate, the late Sultan of Sulu, Sultan Jamalul Kiram II against Malaysia (the “Award”) that was handed down by a sole arbitrator had created much discussion in the international public and private law arena. Following the issuance of the n Award, Malaysia challenged the Award in the Paris Court of Appeal and successfully stayed the Award’s enforcement in France on July 12. During the same time, on July 11, two Luxembourg-registered subsidiaries of the Malaysian state oil company Petronas were served with ‘saisie-arret’ by bailiffs, acting on behalf of the heirs to the Sultanate of Sulu, pending any appeal by Petronas against the seizure. Putting aside the international law discussion, this paper focuses on the international private law setting of international commercial arbitration and its significance to the case study. This paper concentrates on three issues derived from international commercial arbitration regarding the case study of the Award, its longform title “Nurhima Kiram Fornan, Fuad A Kiram, Sheramar T Kiram, Permaisuli Kiram-Guerzon, Taj-Mahal Kiram-Tarsum Nuqui, Ahmad Narzad Kiram Sampang, Jenny Ka Sampang and Widz-Raunda Kiram Sampang v Malaysia”, namely, the arbitration clause and seat, the issue of third-party funding and ethical international commercial arbitration. This paper employed the qualitative content analysis research method in analysing the issues related to international commercial arbitration using primary and secondary sources. Among the primary sources used in this paper include case law, arbitration award, agreement, government gazettes, memoranda, the New York Convention and UNIDROIT principles. The secondary sources include articles, books, newspaper reports, and other secondary sources available online and offline. The findings of the article conclude that there are divergences in the principles applied in the Award regarding arbitration clause and seat, that the case is motivated by third-party funding which calls for further ethical considerations and discussion in international commercial arbitration.